2013 IEEE Innovative Smart Grid Technologies-Asia (ISGT Asia) 2013
DOI: 10.1109/isgt-asia.2013.6698758
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of grid integrated solar photovoltaic systems under the tropical environment

Abstract: As the output from the solar PV systems varies significantly with technologies, designs and prevailing weather parameters, their evaluation under actual field conditions is important in identifying their real performance characteristics. In this paper, comparative performances of six different PV systems connected to a 1.2 MWp grid integrated solar farm are presented. The solar technologies considered are the single crystalline (sc-Si), poly crystalline (mc-Si), micro crystalline (nc-Si/a-Si), amorphous silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…notably: Ismail et al (2013) compared the performance of six 200-kWp PV systems in Brunei Darussalam; Zinber et al (2010) compared the performance of 24 1-kWp PV systems in Stuttgart, Germany, and Nicosia, Cyprus;and Friesen et al (2011) compared the performance of 13 PV modules in Canobbio, Switzerland. Comparing PV module data provides potentially lower uncertainty in results, because PV module power ratings and coefficients can be more accurately determined than those for PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…notably: Ismail et al (2013) compared the performance of six 200-kWp PV systems in Brunei Darussalam; Zinber et al (2010) compared the performance of 24 1-kWp PV systems in Stuttgart, Germany, and Nicosia, Cyprus;and Friesen et al (2011) compared the performance of 13 PV modules in Canobbio, Switzerland. Comparing PV module data provides potentially lower uncertainty in results, because PV module power ratings and coefficients can be more accurately determined than those for PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, such as soiling, mismatch and shadowing, also aggravate the L C . Ismail et al (2013) reported a much higher L C for two 200 kWp GCPV systems based on a-Si and poly-Si in Brunei, where the L C were 18.2% and 26.7%. Meanwhile, the corresponding L C of the two systems in ETSIAAB GCPV plant from 2014 to 2015, were 8.4% and 7.5%, respectively.…”
Section: Energy Conversion Chainmentioning
confidence: 95%